2016
DOI: 10.1007/s10803-016-2865-7
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Character Strengths in Adults with Autism Spectrum Disorder Without Intellectual Impairment

Abstract: In the current study, we assessed character strengths in individuals with autism spectrum disorder (ASD, n = 32) and neurotypical controls (n = 32) using the Values in Action Inventory (VIA-IS, Peterson and Seligman 2004) and explored associations with levels of satisfaction with life (SWL). The most frequently endorsed signature strengths (i.e., five top-ranked strengths within an individual's strength ranking) were emotional (humour, love) and interpersonal strengths (kindness, fairness) in the control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…They found a few significant differences, with people with ASC more likely to have creativity as a key strength, and with more common strengths in those without ASC described as love (defined as "valuing close relationships with others" [46] (Table 1)) and humour. However, they found no significant differences in the presence of twenty-one other character strengths [44].…”
Section: Strengths and Skills Of People With Ascmentioning
confidence: 86%
See 1 more Smart Citation
“…They found a few significant differences, with people with ASC more likely to have creativity as a key strength, and with more common strengths in those without ASC described as love (defined as "valuing close relationships with others" [46] (Table 1)) and humour. However, they found no significant differences in the presence of twenty-one other character strengths [44].…”
Section: Strengths and Skills Of People With Ascmentioning
confidence: 86%
“…It is also important to remember that in many areas people with ASC have no advantages or deficits compared to neuro-typical people and perform in very similar ways. For example, Kirchner et al [44] analysed character strengths, using the Values in Action Inventory [45], in individuals with and without a diagnosis of autism. They found a few significant differences, with people with ASC more likely to have creativity as a key strength, and with more common strengths in those without ASC described as love (defined as "valuing close relationships with others" [46] (Table 1)) and humour.…”
Section: Strengths and Skills Of People With Ascmentioning
confidence: 99%
“…Adults with ASD have many strengths that can contribute to job performance, such as attention to detail, logical reasoning, reliability, and focus (Kirchner et al, 2016;Lorenz & Heinitz, 2014). Some managers have also expressed positive opinions on integrating employees with ASD, even when they needed considerable support to function in the workplace (Hagner & Cooney, 2005).…”
Section: Program Evaluation Of a Community Organization Offering Suppmentioning
confidence: 99%
“…Studies examining personality disorder comorbidity in adults with ASD found high prevalence rates for especially cluster A and C personality disorders [ 22 , [25] , [26] , [27] ], ranging from 48% [ 27 ] to 62% [ 25 ]. To our knowledge, Kirchner et al [ 28 ] were among the first to examine character strengths in adults with ASD, finding open-mindedness, authenticity, love of learning, creativity and fairness as the most frequent signature strengths.…”
Section: Introductionmentioning
confidence: 99%